STUDI KASUS FAKTOR-FAKTOR YANG MEMPENGARUHI HASIL BELAJAR MATEMATIKA DI SD NEGERI 01 NANGA MERAKAI - Wibowo, Dwi Cahyadi; Ocberti, Lhadyza; Gandasari, Adriana (Jurnal Ilmiah Aquinas, 2021)
The purpose of this research is to describe the factors that affect mathematics learning outcomes in class V SD Negeri 01 Nanga Merakai Academic Year 2019/2020. This research uses qualitative research methods with a qualitative descriptive approach with a case study research form.Â  The research sample consisted of 16 student of class 5th at public elementary school 01 Nanga Merakai. Data collection tools in the form of interview guidelines, questionnaires and documentation studies. Data analysis through several stages of data collection, data persentation, data reduction and conclusion drawing. The results showed that (1) Inhibiting factors affecting mathematics learning outcomes were divided into two factors, namely internal factors and external factors. (2) Â Supporting factors for mathematics learning outcomes, the research results are divided into two, namely internal factors and external factors.